The Sense Project: An Innovative Model for Sexualities Education Partnerships Between Community-Based Educators and Schools (LEARNing Landscapes, 2012)
Significant changes in the way sexual health curricula would be imagined and taught occurred after the 2005 educational reforms were implemented in Quebec. Based on data collected over five years of program evaluations and interviews with community-based educators and teachers, we examine the innovative sexual health education model of the "Sense Project," developed by Head & Hands / À Deux Mains in Montreal, and the overwhelmingly positive youth response to our program in schools and in other community youth organizations. Here we discuss some of the challenges, possibilities, and strategies involved with establishing partnerships between schools and community-based sexualities educators.
Keywords: sexual health; education; youth; Quebec; program evaluation; interview